FAKTOR – FAKTOR YANG MEMENGARUHI KUALITAS LAPORAN KEUANGAN PADA PENGADILAN SEWILAYAH BANTEN - Wulyan, Dewi (Pascasarjana Universitas Sultan Ageng Tirtayas, 2017)
This study aims to determine the factors that effect the quality of financial statements to the court area Banten. Data obtained from 13 courts in Banten region with purposive sampling method. The results of this study indicate that the competence of human resources has a significant positive effect on the quality of financial statements, institution accounting system has a significant positive effect on the quality of financial statements, the utilization of information technology has a significant positive effect on the quality of financial statements, the aplication of internal control system has a significant positive effect on the quality of financial statements, and organizational commitment negatively affect the quality of financial statements.Â Keywords : Competence of Human Resources, Institution Accounting System, Information Technology, Internal Control System, Organizational Commitmen